Chemical Etching, AFM, Laser Damage Threshold, and Nonlinear Optical Studies of Potential Nonlinear Optical Crystal: Bis (L-Glutamine) Potassium Nitrate - Redrothu Hanumantharao; S. Kalainathan (Journal of Chemistry)
A novel semiorganic nonlinear optical crystal bis (L-glutamine) potassium nitrate (BGPN) grown by slow evaporation technique at ambient temperature. The grown crystal surface has been analyzed by chemical etching and atomic force microscopy (AFM) studies. Amplitude parameters like area roughness, roughness average, valley height, valley depth, peak height, and peak valley height were measured successfully from AFM studies. Etching studies were carried out by various solvents like water, methanol and ethanol. The etching study indicates the occurrence of different types of etch pit patterns like striations and steplike pattern. The laser damage threshold energy has been measured by irradiating laser beam using a Q-switched Nd: YAG laser (1064 nm). Second harmonic generation (SHG) studies have been performed by famous Kurtz powder technique with reference to standard potassium dihydrogen phosphate single crystals (KDP). It is found from this technique that SHG efficiency of BGPN is in comparison to that of standard KDP crystals.